Novosti . Novosti . News . Новости - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
This program was broadcast by the state television (Moscow) in the USSR and recorded by the Radio Liberty Monitoring Unit in Munich as part of their effort to track and analyze the official media of the republics of the Soviet Union. Передача государственного телевидения (Москва, СССР) была записана отделом мониторинга радиостанции Свобода (Мюнхен) как часть проекта по анализу официальных средств информации республик Советского Союза. Recognition of Palestine as an independent state; interview with the representatives of the Soviet-Chinese Friendship Association. Series description: A program of Channel One, broadcasted since February 10, 1986. It surveys the information from the passed part of the day, including sport news and weather forecast. Broadcasted several times a day with the interval 2-3 hours. Until October 14, 1990, the program was called "News." Before 1991 the program was produced by the Studio of information programs of the Central Television, and from 1991 - by the newly crated Information Tevevision Agency. In 1986-1994 the program's timing was from 6 to 21 minutes. From October 1991, evening broadcasts were anchored by Tatiana Komarova, Sergei Medvedev, Irina Mishina, and Pavel Kasparov, and the night broadcasts were anchored by Mikhail Osokin and Dmitrii Kiselev. From February 1992 to September 1993 Sergei Dorenko was the anchorman of the evening issue instead of Pavel Kasparov. Признание независимости Палестинского государства; интервью с представителем Общества китайско-советской дружбы. Описание серии: Программа Первого канала, выходящая в эфир с 10 февраля 1986 года по сей день. Представляет собой обзор информации за прошедшую часть дня, включая новости спорта и прогноз погоды. Выходит в эфир несколько раз в день с интервалом 2-3 часа. До 1991 года программа выпускалась Студией информационных программ Центрального Телевидения, с 1991 года - вновь созданным Информационным Телевизионным Агенством. В 1986-1994 годах хронометраж программы составлял от 6 до 21 минуты. Ведущими вечерних выпусков с октября 1991 года стали Татьяна Комарова, Сергей Медведев, Ирина Мишина, Павел Каспаров, ведущими ночных выпусков — Михаил Осокин и Дмитрий Киселёв. С февраля 1992 года по сентябрь 1993 года ведущим вечернего выпуска программы стал Сергей Доренко вместо Павла Каспарова.